In vitro Antioxidant Activities of Ethanol, Ethyl Acetate and n-Hexane Extracts of Mangifera indica Leaves - Ibrahim, Yunusa O.; Busari, Musa B.; Yusuf, Ruqayyah S.; Hamzah, Rabiat U. (Tanzania Journal of Science, 2020)
Mangifera indica leaves have been in use in folk medicine since ancient time, for the treatment and/or management of numerous health complications. In this study, total phenols and flavonoids contents, as well as in vitro antioxidant activities of ethanol, ethyl acetate and n-hexane extracts of M. indica leaves were determined and compared. The in vitro antioxidant activities were determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, ferric reducing antioxidant power, and inhibition of lipid peroxidation assays, respectively. The total phenols were found to be present in the descending order of; ethanol extract > ethyl acetate extract > n-hexane extract, while flavonoids were observed in the descending order of; n-hexane extract > ethanol extract > ethyl acetate extract. The maximum percentage DPPH radical scavenged (at 100 µg/mL), ferric reducing power (at 400 µg/mL) and inhibitory activity on lipid peroxidation (at 400 µg/mL) exhibited by the ethanol extract (94.40%, 88.73%, and 84.05%, respectively) were significantly greater (p < 0.05) than the ethyl acetate extract (79.46%, 68.74%, and 79.73%, respectively at 400 µg/mL) as well as n-hexane extract (45.30%, 58.79%, and 67.78%, respectively at 100 and 400 µg/mL). It can be concluded that the extracts possess anti-oxidant activities and may be employed in the treatment and/or management of oxidative stress related diseases.